2013
DOI: 10.1111/liv.12415
|View full text |Cite
|
Sign up to set email alerts
|

Altered Frequencies of Dendritic Cells and IFN‐γ‐secreting T Cells with Granulocyte Colony‐Stimulating Factor (G‐CSF) Therapy in Acute‐on‐Chronic Liver Failure

Abstract: G-CSF therapy increased the frequencies of dendritic cells and reduced IFN-c secreting CD8 T cells with improved clinical severity indices. Decreased IFN- c production may contribute to reduced hepatocellular damage in ACLF patients.Our observations support the basis for further use of G-CSF therapy as immune modulator in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 31 publications
0
46
1
1
Order By: Relevance
“…It would be possible to address key targets to prevent organ damage, thereby inhibiting progression toward liver failure, which will ultimately reduce the requirement for liver transplantation. We have recently shown that reduction in intrahepatic dendritic cells and increased interferon gamma (IFN-γ)-producing CD8+ T cells has an important role in hepatocellular injury which correlates with high mortality in ACLF (3). …”
Section: Introductionmentioning
confidence: 99%
“…It would be possible to address key targets to prevent organ damage, thereby inhibiting progression toward liver failure, which will ultimately reduce the requirement for liver transplantation. We have recently shown that reduction in intrahepatic dendritic cells and increased interferon gamma (IFN-γ)-producing CD8+ T cells has an important role in hepatocellular injury which correlates with high mortality in ACLF (3). …”
Section: Introductionmentioning
confidence: 99%
“…The frequency of intrahepatic myeloid and plasmacytoid dendritic cells is reduced with increased interferon gamma producing CD8 T cells in patients with ACLF. Decreased frequency of DCs and high IFN-c levels correlate with poor patient survival [75].…”
Section: Sepsis In Aclfmentioning
confidence: 99%
“…Moreover, circulating myeloid and plasmacytoid dendritic cells and T cells were shown to increase following G-CSF therapy, while IFN-γ production by CD8-T cells was decreased [75,77]. These findings have also been documented in a cohort of patients with HBV-associated ACLF [78].…”
Section: Gut Microbiotamentioning
confidence: 64%